2020
DOI: 10.1371/journal.pone.0230085
|View full text |Cite
|
Sign up to set email alerts
|

Emerging partner violence among young adolescents in a low-income country: Perpetration, victimization and adversity

Abstract: Background Intimate partner violence (IPV) is prevalent in high-as well as low-income contexts. It results in a substantial public health burden and significant negative socioeconomic and health outcomes throughout the life-course. However, limited knowledge exists about IPV during early adolescence. This period is critical during the transition to adulthood for at least two reasons: it is when the majority of adolescents in low-income countries first encounter dating, sexuality and partnerships, often with ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
1
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 82 publications
6
40
1
16
Order By: Relevance
“…With regard to more serious behaviors like sexual and physical violence, women use physical attacks, while men use sexual behaviors, although it should be underlined that these are not so prevalent, but they are present. These data coincide with studies by other authors who report in their investigations that women use physical violence to a greater extent and men are more prone to using sexual violence [ 4 , 14 , 18 , 31 , 59 ].…”
Section: Discussionsupporting
confidence: 91%
“…With regard to more serious behaviors like sexual and physical violence, women use physical attacks, while men use sexual behaviors, although it should be underlined that these are not so prevalent, but they are present. These data coincide with studies by other authors who report in their investigations that women use physical violence to a greater extent and men are more prone to using sexual violence [ 4 , 14 , 18 , 31 , 59 ].…”
Section: Discussionsupporting
confidence: 91%
“…Women exercise more psychological and physical violence (and also experience it). Consequently, men present higher levels of physical victimization and exercise more sexual violence (Cortés-Ayala et al, 2015;García-Carpintero et al, 2018;Kidman & Kohler, 2020;Pazos et al, 2014;Rodríguez, 2015;Rubio-Garay et al, 2017). In addition, we have observed that, in the absence of physical victimization, psychological victimization occurs, mainly related to alienation, especially in women.…”
Section: Discussionmentioning
confidence: 81%
“…According to the last results of the Spanish National Statistics Institute (National Statistics Institute, 2019), the number of young people reported for gender violence, compared with the previous year, increased by 14.1% at ages 18 to 19 and by 11.9% at ages 25 to 29. Therefore, studies are focusing on the youngest couples because, in this stage, risky behaviors prevail (Borrás et al, 2017) and, in consequence, violent dynamics increase and start to be considered acceptable (Kidman & Kohler, 2020). Dating violence develops differently than adult intimate partner violence.…”
Section: Introductionmentioning
confidence: 99%
“…Although perpetration of GBV transcends socioeconomic, educational, religious, and cultural lines, its prevalence is especially pronounced in sub-Saharan Africa, where accounts of intimate partner violence (IPV) amongst ever-married/partnered women aged 15–49 years old, for instance, supersede worldwide averages by 22% [ 3 , 4 ]. Moreover, while low- and middle-income countries (LMICs) carry a greater burden of GBV, research on human rights violations in these settings, especially for adolescent girls, disproportionately lags behind efforts in high-income countries [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent girls are particularly vulnerable to GBV, their age and social status amplifying power imbalances and further limiting their autonomy [ 1 , 2 , 3 , 5 , 6 ]. The physical and mental toll of GBV greatly impacts survivors’ behaviors and lifetime health risks.…”
Section: Introductionmentioning
confidence: 99%